Numerical and Experimental Analysis of the Honing Texture on the Lubrication Performance of Piston Ring–Cylinder Liner Tribosystem. Issue 6 (2nd November 2019) - Li, Tongyang; Lu, Xiqun; Ma, Xuan; Xu, Hanzhang; Jiao, Bowen; Zou, Dequan
Abstract: A lubrication model of the piston ring–cylinder liner tribosystem taking account of the honing texture was established in this study. The impact of honing texture parameter, which was characterized by its crossing angle α, groove depth dp, and groove density de, was investigated experimentally and numerically to evaluate the lubrication performance of this tribosystem. The experiment was performed on a reciprocating workbench involving piston ring and cylinder liner segments to verify this model, and the calculated average friction coefficient was in good agreement with the measured data. The numerical analysis of the instantaneous friction coefficient (IFC), minimum oil film thickness (MOFT), and load-carrying capacity of oil (LCCO) were applied to analyze the effect of different honing texture parameters using single-factor analysis. Furthermore, the friction force at the dead center was optimized by multiple-factor analysis and reached the minimum value when α  = 40°, dp = 3 μm, and de = 1.5 mm −1 . Finally, analysis of parameter sensitivity showed that honing density has the most significant influence on lubrication performance.